2009
DOI: 10.1002/cbic.200800741
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Glycosylation of Triazole‐Linked GlcNAc/Glc–Peptides: Synthesis, Stability and Anti‐HIV Activity of Triazole‐Linked HIV‐1 gp41 Glycopeptide C34 Analogues

Abstract: Endoglycosidase-catalyzed transglycosylation of triazole-linked glucose (Glc) and N-acetylglucosamine (GlcNAc)-containing dipeptides and polypeptides was achieved, using synthetic sugar oxazoline as the donor substrate. It was found that both N- and C-linked Glc/GlcNAc-containing triazole derivatives were effective substrates for endo-β-N-acetylglucosaminidase from Arthrobacter (Endo-A) for transglycosylation, demonstrating a broad acceptor substrate specificity for Endo-A. This chemoenzymatic method was succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 69 publications
0
25
0
Order By: Relevance
“…Deprotection of the acetyl groups on the carbohydrate moiety to afford 24 was successfully performed with catalytic amounts of K 2 CO 3 in MeOH under carefully controlled pH conditions. [14] No epimerization was observed under these conditions by 1 H and 13 C NMR or by analysis of the LC-MS chromatograms. Finally, conditions for the solid-phase synthesis of the glycopeptides were explored.…”
Section: Resultsmentioning
confidence: 91%
“…Deprotection of the acetyl groups on the carbohydrate moiety to afford 24 was successfully performed with catalytic amounts of K 2 CO 3 in MeOH under carefully controlled pH conditions. [14] No epimerization was observed under these conditions by 1 H and 13 C NMR or by analysis of the LC-MS chromatograms. Finally, conditions for the solid-phase synthesis of the glycopeptides were explored.…”
Section: Resultsmentioning
confidence: 91%
“…Whereas changes at the C6 did not alter enzyme activity, configuration inversion at the 29 and/or 49-hydroxyls of the Man residue caused total loss of activity (60). In another study, Huang et al showed that native N-linked and triazolelinked GlcNAc were tolerated by Endo-A as acceptor entities (61). Another report by Rising et al (62) showed excellent (91%) yields for the transglycosylation of Man-a-1,3-Glc-b-1,4-GlcNAc-oxazoline using Endo-M.…”
Section: Chemoenzymatic Synthetic Strategiesmentioning
confidence: 93%
“…Several bacterial and fungus endoglycosidases, including Endo-A, Endo-M, Endo-D, Endo-S, and Endo-F3, which possess distinct glycan and acceptor substrate specificity, have been converted into glycosynthases for synthetic applications (Wang and Lomino, 2012). These enzymes have been used for the synthesis of large and complex glycopeptides including HIV-1 glycopeptide antigens (Amin et al, 2013; Huang et al, 2009a; Huang et al, 2010b; Li et al, 2005a; Li et al, 2005b); for glycosylation remodeling to produce homogeneous glycoproteins carrying natural and selectively modified (e.g., azide-tagged or fluorinated) N-glycans (Amin et al, 2011; Huang et al, 2009b; Huang et al, 2010a; Li et al, 2006; Ochiai et al, 2008; Orwenyo et al, 2013; Schwarz et al, 2010; Umekawa et al, 2010); and for glycoengineering of intact IgG antibodies (Fan et al, 2012; Huang et al, 2012; Wei et al, 2008; Zou et al, 2011). This chemoenzymatic method was also successfully combined with NCL for synthesizing full-size glycosylated proteins (Asahina et al, 2013; Hojo et al, 2012).…”
Section: Major Approaches For Glycoprotein Synthesismentioning
confidence: 99%